2011
DOI: 10.1017/s0033291711000201
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled trial on the efficacy and tolerability of sertraline in Iranian veterans with post-traumatic stress disorder

Abstract: The results of this study suggest that sertraline can be an effective, safe and tolerable treatment for combat-related PTSD in Iranian veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…41 However, the maximum dose reached in all groups treated with antidepressants was low compared with other studies. 42,43 It would have been an obvious advantage if the medicine adherence of patients and serum concentrations had been checked with blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…41 However, the maximum dose reached in all groups treated with antidepressants was low compared with other studies. 42,43 It would have been an obvious advantage if the medicine adherence of patients and serum concentrations had been checked with blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen new studies were found from our database search. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The remaining 35 were found in previous reviews. An additional 28 studies were identified from the NICE guidelines, of which five did not meet our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Data with fluoxetine are mixed, with both positive [960-962] and negative [963-965] RCTs (Level 1, conflicting). Similarly, RCTs with sertraline have yielded both positive [971,972,975,976,978] and negative [973,974,977] results (Level 1, conflicting). However, there appear to be sufficient data from the larger RCTs to suggest that these agents can be effective first-line options.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%